The dilemma of filing charges in crimes of violence against women or against a family member - Valdivia Valdarrago, Mariano Rodolfo (2022)
Filing charges is one of the issues that the national case law has considered important, due to the fact that the interpretation or enforcement of the law poses a number of problems related to the precision required to attribute a particular behavior. The implementation of Act No. 30364 –the Act to Prevent, Punish and Eradicate Violence against Women and Family Members-, has not ignored this fact since it meant a positive step taken by the Peruvian State to combat violence against these vulnerable groups and which to a great extent involves the modification of our culture and customs. In this scenario, criminal definitions have been incorporated in the Criminal Code to criminalize these aggressions; however, in their evolution, said behaviors have also incorporated a high content of norms and values, which precisely give rise to their interpretation. Such is the case of Legislative Decree No. 1323, that amended Criminal Code Section 122-B, and which has posed a number of problems for the justice operators when making a proper filing of charges, since its content alternatively consigns a woman in her capacity as such on the one hand and a family member on the other, as subjects of protection, a condition that a woman who forms part of a family already possesses. Thus, based mainly on field experience, we propose a reflection on the focus of the filing of charges in crimes of violence against women or against a family member.